Prefabricerade stödmurar i betong - Pettersson, Linda (2007)
This is a booklet with information and inspiration about precast retaining walls. The three chapters contain information about concrete as a material, how the surface of the wall can be altered, and a chapter with ideas for a new precast wall. I have obtained information through books, interviews, lectures and fairs. The retaining walls on the market do not correspond to the requirements of the Landscape Architects I have interviewed. I have therefore considered their opinions in the chapter containing my new ideas for new retaining walls. I have come up with two different ideas to alter the surface of retaining walls. Except from learning a lot about concrete and retaining walls I have also made useful contacts both within the Architectural proffession and with people in the concrete industry as well as with artists. My hope is that the booklet will be used as a source for inspiration and help during the everyday work as a Landscape Architect. The booklet is made as a degree thesis in Landscapearchitecture at the institution SOL at SLU Ultuna.